Interactive Multi-Robot Painting Through Colored Motion Trails - Santos, María; Notomista, Gennaro; Mayya, Siddharth; Egerstedt, Magnus (Frontiers in Robotics and AI, 2020)
In this paper, we present a robotic painting system whereby a team of mobile robots equipped with different color paints create pictorial compositions by leaving trails of color as they move throughout a canvas. We envision this system to be used by an external user who can control the concentration of different colors over the painting by specifying density maps associated with the desired colors over the painting domain, which may vary over time. The robots distribute themselves according to such color densities by means of a heterogeneous distributed coverage control paradigm, whereby only those robots equipped with the appropriate paint will track the corresponding color density function. The painting composition therefore arises as the integration of the motion trajectories of the robots, which lay paint as they move throughout the canvas tracking the color density functions. The proposed interactive painting system is evaluated on a team of mobile robots with different experimental setups in terms of paints given to the robot team to highlight the effects and benefits of considering heterogeneous teams when there is a limited availability of painting resources.